Pancreatic Pseudocyst: Therapeutic Dilemma - Khanna, A. K. (Hindawi Publishing Corporation, 2012)
Pancreatic pseudocyst develops in both acute and chronic pancreatitis. It is an entity likely to either remain asymptomatic or develop devastating complications. Despite being diagnosed easily, treatment exercise is still at crossroads whether in the form of internal or external drainage or endoscopic, laparoscopic, or open intervention with a good radiological guidance. The therapeutic dilemma whether to treat a patient with a pancreatic pseudocyst, as well as when and with what technique, is a difficult one. This paper is intended to get information about diagnostic and therapeutic exercises most appropriate for acute and chronic pancreatic pseudocyst.